Craniotomy vs. Burr Hole in the Management of Chronic Subdural Hematoma: A Literature Review - Firdaus, Alpasca; Danang Bagus, Untoro (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2025)
Introduction: Chronic subdural hematoma (CSDH) is a common condition, especially in the elderly, often requiring surgical intervention. Burr hole drainage and craniotomy are the two main surgical approaches. However, the optimal technique remains debated due to differences in recurrence rates, complications, and outcomes. Methods: A comprehensive literature review was conducted using databases such as PubMed, Scopus, and Google Scholar to compare burr hole drainage and craniotomy in the management of CSDH. Studies were selected based on relevance to surgical technique, recurrence, complications, and patient outcomes. Results and Discussion: Burr hole drainage is less invasive, associated with shorter operative time, reduced hospital stay, and fewer complications. It is widely considered the first-line surgical option. However, some studies report higher recurrence rates compared to craniotomy. Craniotomy, while more invasive, may be more effective in cases with organized or recurrent hematomas, offering more thorough evacuation. It carries a higher risk of complications, particularly in elderly or comorbid patients. Clinical decision-making often depends on hematoma characteristics and patient condition. Conclusion: Both burr hole drainage and craniotomy are effective for CSDH, but each has distinct advantages and drawbacks. Burr hole drainage is generally preferred due to its safety and efficacy, while craniotomy may be reserved for complex or recurrent cases. A patient-centered approach considering clinical and radiological factors is essential. Further randomized studies are needed to refine surgical guidelines. Keywords: Chronic subdural hematoma, burr hole drainage, craniotomy, neurosurgery, recurrence, surgical outcomes, complications